1979
DOI: 10.1099/00221287-111-1-121
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxazinone Biosynthesis: Accumulation of a Precursor, 4-Methyl-3-hydroxyanthranilic Acid, by Mutants of Streptomyces parvulus

Abstract: Mutants of Streptomyces parvulus that are blocked in the synthesis of the phenoxazinonecontaining antibiotic, actinomycin, were isolated by the ' agar piece ' method (after ultraviolet irradiation or treatment with 8-methoxypsoralen plus near-ultraviolet light). Radiolabelling experiments in conjunction with paper, thin-layer and column chromatography revealed that 4-methyl-3-hydroxyanthranilic acid (MHA) is a major metabolite accumulated by these mutants. Studies in vitro and in vivo provided evidence that MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…It can be seen that radioactive products were eluted at each of the three acetic acid concentrations used in the experiment. Previous studies have demonstrated that MHA is eluted from Dowex 1 by 6 M acetic acid (17,19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that radioactive products were eluted at each of the three acetic acid concentrations used in the experiment. Previous studies have demonstrated that MHA is eluted from Dowex 1 by 6 M acetic acid (17,19).…”
Section: Resultsmentioning
confidence: 99%
“…While the direct role of this enzyme in actinomycin biosynthesis has not been demonstrated, there is strong evidence for the involvement of MHA as an intermediate in the biosynthetic pathway (10,12,17). Katz and co-workers (2, 16) have characterized several enzymes in the tryptophan catabolic pathway which participate in the conversion of that amino acid to the aromatic precursors of the actinomycin molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A putative pathway for actinomycin biosynthesis was proposed several years ago (50), and biochemical, physiological, and genetic studies have confirmed the essential details of that pathway. Five enzymes from S. antibioticus, Streptomyces chrysomallus, and Streptomyces parvulus have been isolated and characterized to demonstrate their involvement in the actinomycin biosynthetic pathway (6,11,22,23,(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…These pioneering studies by Katz and Weissbach also demonstrated that the chromophore of actinomycin D, a phenoxazinone ring, is derived from the catabolism of tryptophan (19). Thus, 3-hydroxykynurenine is converted to 3-hydroxyanthranilic acid, and the latter intermediate is methylated to form 4-methyl-3-hydroxyanthranilic acid, the precursor of the phenoxazinone ring (28).…”
mentioning
confidence: 99%